Long Term Care Partnerships: Are they 'Fit for Purpose'? - Savannah Bergquist; Joan Costa-i-Font; Katherine Swartz (Center for Economic Studies and ifo Institute (CESifo), 2015)
The risk of high costs of long-term care services and supports (LTSS) is one of the largest uninsured risks for American families and a major challenge to the sustainability of Medicaid. To address the latter, the long-term care partnership (LTCP) program was an initiative designed to encourage middle-class individuals to purchase private long-term care insurance to cover at least the non-catastrophic costs of LTSS. The goal was to defer the time when an individual would become eligible for Medicaid to pay her LTSS expenses, and thereby reduce Medicaid expenditures. This paper exploits two unique sources of variation in the effects of LTCP, (i) the long term effects in the four states that were allowed to implement partnership programs in 1993-4, and (ii) the short-term effects in the states that implemented LTCP programs after 2005. Given the progressive development of the LTCP, we identify differences in trends in insurance uptake and Medicaid long-term care expenditures and claims. Both sources of variation suggest LTCP programs modestly stimulated LTC insurance uptake and slowed Medicaid LTC expenditures and claims trends.
Keywords: H31; I18; I38; J14; 330; Long Term Care (LTC) Insurance; LTC Partnerships (LTCP); subsidization; medicaid; differences in trends; catastrophic costs